THE VALUE OF RELIGIOUS MODERATION EDUCATION IN THE TRADITION OF ROKAT TASE' IN THE VILLAGE - Holik, Abdul; Al Humaidy, Mohammad Ali; Nur Efendy, Agik; Maimun; Listiana, Heni; hamdani; Amin, Syaiful (Al-Ishlah: Jurnal Pendidikan Islam, 2024)
Background: The Rokat Tase' tradition is a ritual of gratitude and prayers for safety by the people of Tlontoh Rajeh Village, expressing gratitude for the abundant sea harvest. It reflects local wisdom and a close relationship with nature and Islamic teachings. Research Objectives: This research aims to explore how Rokat Tase' has become a symbol of religious moderation in Tlontoh Rajeh Village, identifying factors supporting the sustainability of this tradition and its impact on local social and economic development. Methods: Employing a qualitative approach with descriptive methods, the study involved participatory observation, in-depth interviews with community leaders and residents, and a literature review on Rokat Tase' and religious moderation. Data were analysed through triangulation to ensure the validity of findings.The study found that Rokat Tase' in Tlontoh Rajeh Village not only strengthens social solidarity and cultural identity but also embodies harmony between Islamic teachings and local values. Involving all layers of society regardless of social or religious differences, the ritual demonstrates balance and tolerance, core elements of religious moderation. Conclusions: The Rokat Tase' tradition in Tlontoh Rajeh Village is a manifestation rich in spiritual, social, and religious moderation values. Through gratitude for the blessings of the sea and respect for local wisdom, the tradition not only strengthens social bonds but also provides a concrete example of how communities can live harmoniously in diversity, appreciate differences, and embrace educational values such as religious education, social education, and cultural education.